Energy harvesting approach to utilize the dissipated energy during hydraulic active suspension operation with comfort oriented control scheme. (1st June 2021) - Sathishkumar, P.; Wang, Ruochen; Yang, Lin; Thiyagarajan, J.
Abstract: Even though the active suspension provides enhancement in comfort and road-holding in addition to vehicle safety and handling, energy demand is one of the major problem in commercialization. Therefore, energy harvesting from the vehicle active suspension brings greater significance to the energy management and vehicle dynamics research. The consumption of more power occurs by hydraulic active suspension for the process of fluid actuation into chamber through the control valves and instantaneously significant amount of power is being dissipated by another chamber of the same actuator. Hence, this study propose a novel approach to harvest energy from the dissipating energy of active suspension through the control valve. In order to ensure the comfort and road-holding, model predictive control effort was provided to the hydraulic control valve. Dissipated fluid during the operation was directed to the hydraulic motor to generate the power and the influence of hydraulic power generation unit is being compensated by two new approaches. For the numerical simulation, active suspension integrated four wheel vehicle model was developed in AMESim and its control valve is controlled in Matlab co-simulation environment. The 1D mapped variable and constant resistance energy harvesting schemes provided the maximum RMS power of 1385.4 W & 1427.6 W in the D-class road at 28 m/s velocity. Also, the results of both proposed energy harvesting approaches showed that the comfort oriented characteristics of active suspension such as actuator effort, comfort and road-holding were not affected. Highlights: Utilization of dissipated energy from hydraulic active suspension was proposed. Energy harvesting was achieved without compromising the comfort and road holding. 1.42 kW power from HCV dissipation was harvested using mapped resistance ASS. It is convenient to incorporate HPG unit in ASS for reducing the energy demand.